Evaluating Ethical Responsiveness in Police Services Through Public Complaints: A Virtue Ethics Case Study at Polda Metro Jaya, Indonesia - Rinaldi Hastomo; Chryshnanda Dwilaksana; Maria Puspitasari (UIN Sunan Gunung Djati, 2025)
This study investigates the ethical dimensions of police public service delivery at the Integrated Police Service Centre (SPKT) of Polda Metro Jaya, focusing on the persistent gap between procedural compliance and ethical responsiveness. The research aims to identify the root causes of weak ethical implementation and to propose reform strategies grounded in virtue ethics. Employing a qualitative case study design, the study draws on data collected through in-depth interviews with officers and service users, 28 days of participant observation, and document analysis of police regulations and standard operating procedures. Thematic analysis was used to interpret recurring patterns in service behaviour and institutional culture. The findings reveal that while officers fulfil administrative requirements effectively, their interactions with the public often lack empathy, attentiveness, and moral judgement. Structural constraints, legalistic SOPs, and the absence of virtue-based training contribute to the erosion of ethical service culture. The study argues that the core issue is not regulatory deficiency, but the underdevelopment of moral character among police personnel. As a contribution to both theory and practice, the research introduces a comprehensive virtue ethics-based reform framework encompassing leadership, training, organisational culture, and procedural revision. The originality of this study lies in its explicit application of Aristotelian virtue ethics as a corrective model to address ethical stagnation in police service—a perspective rarely explored in Indonesian public administration scholarship.